7000 Eichen - Bastian, Heiner; Kunsthalle Tübingen (Bern : Bentili Verlag, 1985)
Barceló, Miquel ; Basquiat, Jean-Michel ; Beuys, Joseph ; Bömmels, Peter ; Brown, James ; Chia, Sandro ; Clemente, Francesco ; Cragg, Tony ; Cucchi, Enzo ; Dahn, Walter ; Deutsch, David ; Disler, Martin ; Dokoupil, Jiri Georg ; Haring, Keith ; Immendorff, Jörg ; Kapoor, anish ; Koberling, Bernd ; Knoebel, Imi ; Kounellis, Jannis ; Long, Richard ; Marden, Brice ; McLean, Bruce ; Merz, Mario ; Middendorf, Helmut ; Oehlen, Albert ; Oehlen, Markus ; Paladino, Mimmo ; Rauschenberg, Robert ; Salomé ; Schnabel, Julian ; Tannert, Volker ; Twombly, Cy ; Warhol, Andy ; Woodrow, Bill
7000 Eichen, Kunsthalle Tübingen, März 1985
Text English-German
kunstcatalogus